2014
DOI: 10.1158/0008-5472.can-14-1357
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Deletion of AEG-1 Prevents Hepatocarcinogenesis

Abstract: Activation of the oncogene AEG-1 (MTDH, LYRIC) has been implicated recently in the development of hepatocellular carcinoma (HCC). In mice, HCC can be initiated by exposure to the carcinogen DEN, which has been shown to rely upon activation of NF-κB in liver macrophages. Since AEG-1 is an essential component of NF-κB activation, we interrogated the susceptibility of mice lacking the AEG-1 gene to DEN-induced hepatocarcinogenesis. AEG-1-deficient mice displayed resistance to DEN-induced HCC and lung metastasis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 39 publications
1
90
0
Order By: Relevance
“…Interestingly, other factors that support tumor initiation activity seem to work only in the malignant context and are not involved in the regulation of normal adult tissue stem cells. For example, MTDH, an essential factor to support tumor initiation and metastasis in breast, prostate, and liver cancers, is dispensable for embryonic and postnatal development (Robertson et al 2014;Wan et al 2014a,b). Such factors will be ideal candidates for therapeutic targeting to prevent metastasis initiation.…”
Section: Cell Fate Determinants As Regulators Of Micsmentioning
confidence: 99%
“…Interestingly, other factors that support tumor initiation activity seem to work only in the malignant context and are not involved in the regulation of normal adult tissue stem cells. For example, MTDH, an essential factor to support tumor initiation and metastasis in breast, prostate, and liver cancers, is dispensable for embryonic and postnatal development (Robertson et al 2014;Wan et al 2014a,b). Such factors will be ideal candidates for therapeutic targeting to prevent metastasis initiation.…”
Section: Cell Fate Determinants As Regulators Of Micsmentioning
confidence: 99%
“…Subsequently, a recent study using AEG-1-deficient mice found that AEG-1-deficient hepatocytes and macrophages exhibited a relative defect in NF-κB activation; and the IL-6 production and STAT-3 activation were also deficient along with other biological and epigenetic findings in the tumor microenvironment. This demonstrated that AEG-1 supports an NF-κB-mediated inflammatory state that drives HCC development (73).…”
Section: Nf-κb and Phosphatidylinositol 3-kinase (Pi3k)/aktmentioning
confidence: 90%
“…Alb/AEG-1 and AEG-1KO Mice-Generation and characterization of a hepatocyte-specific AEG-1 transgenic mouse (Alb/ AEG-1) and an AEG-1 knock-out (AEG-1KO) mouse have been described previously (12)(13)(14) Patient Samples-Serum samples were collected from hepatitis C virus-HCC patients (n ϭ 23) and 14 healthy volunteers. These studies are approved by the Institutional Review Board of the University of Virginia.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, knockdown of AEG-1 in highly aggressive QGY-7703 cells, expressing high levels of AEG-1, significantly abrogates in vivo tumorigenesis (7,10). As a corollary, an AEG-1 knockout (AEG-1KO) mouse shows profound resistance to diethylnitrosamine/phenobarbital-induced hepatocarcinogenesis and metastasis (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation